Analysis of the pattern, type and the extent of dental services provided to children and youth on the territory of Republic of Serbia - Petrović Bojan; Marković Dejan; Perić Tamara; Marković Evgenija; Vuković Ana; Kilibarda Biljana (Balkan Stomatological Society, 2022)
Background/Aim: The requirements for dental specialties and the number of specialists in each country are unique and strong indicator of the availability and affordability of primary health care for children and adolescents. The aim of this study was to determine the pattern, type and the extent of dental services, as well as the influence of regional factors and data on whether services are provided by a pediatric dentist or general dentist have effect on these parameters, based on information obtained from dentists providing dental care to children and youth. Material and Methods: Within the project "Program for the improvement of oral health of children and youth in the Republic of Serbia", supported by the Ministry of Health of Serbia, a research was conducted among dentists involved in dental care for children and youth in Serbia. Data collection from primary health care facilities was performed through a specially designed questionnaire. A total of 445 questionnaires were collected from dentists from 102 health centers in Serbia in the period June - October 2019. Results: There are significant differences between regions in the pattern, type and the extent of dental services. In the quantitative analysis, there are no significant differences in the type of dental services between pediatric and preventive dentistry specialists and general dentists. Conclusions: The data from the conducted research speak in favor of a large daily workload of dentists who deliver oral health care for children and youth in Serbia. Additional multifactorial analysis, which includes epidemiological data from the region, but also environmental, demographic and cultural parameters of oral health could be the basis for improving the provision of preventive dental and preventive oral care